Rydberg-positronium velocity and self-ionization studies in a 1T magnetic field and cryogenic environment - Antonello, Maddalena; Müller, Simon R.; Zimmer, Christian; Oberthaler, Markus K. (Physical review, 2020)
We characterized the pulsed Rydberg-positronium production inside the Antimatter Experiment: Gravity, Interferometry, Spectroscopy (AE¯gIS) apparatus in view of antihydrogen formation by means of a charge exchange reaction between cold antiprotons and slow Rydberg-positronium atoms. Velocity measurements on the positronium along two axes in a cryogenic environment (≈10K) and in 1T magnetic field were performed. The velocimetry was done by microchannel-plate (MCP) imaging of a photoionized positronium previously excited to the n=3 state. One direction of velocity was measured via Doppler scan of this n=3 line, another direction perpendicular to the former by delaying the exciting laser pulses in a time-of-flight measurement. Self-ionization in the magnetic field due to the motional Stark effect was also quantified by using the same MCP-imaging technique for Rydberg positronium with an effective principal quantum number neff ranging between 14 and 22. We conclude with a discussion about the optimization of our experimental parameters for creating Rydberg positronium in preparation for an efficient pulsed production of antihydrogen.